Live Bacterial Prophylactics in Modern Poultry - Redweik, Graham A. J.; Jochum, Jared; Mellata, Melha (Frontiers in Veterinary Science, 2020)
Commercial poultry farms frequently use live bacterial prophylactics like vaccines and probiotics to prevent bacterial infections. Due to the emergence of antibiotic-resistant bacteria in poultry animals, a closer examination into the health benefits and limitations of commercial, live prophylactics as an alternative to antibiotics is urgently needed. In this review, we summarize the peer-reviewed literature of several commercial live bacterial vaccines and probiotics. Per our estimation, there is a paucity of peer-reviewed published research regarding these products, making repeatability, product-comparison, and understanding biological mechanisms difficult. Furthermore, we briefly-outline significant issues such as probiotic-label accuracy, lack of commercially available live bacterial vaccines for major poultry-related bacteria such as Campylobacter and Clostridium perfringens, as well research gaps (i.e., probiotic-mediated vaccine adjuvancy, gut-brain-microbiota axis). Increased emphasis on these areas would open several avenues for research, ranging from improving protection against bacterial pathogens to using these prophylactics to modulate animal behavior.